The Beliefs of English Teachers and Their Impacts - Fajrinur Fajrinur (English Education Journal, 2018)
Since teaching is a profession that is affected by individual beliefs, so a teacher’s beliefs toward her own profession can affect her teaching performance. The aim of this study was to find out and explain the impacts of the beliefs of teachers of English in Bireuen District. towards their teaching profession. This is a quantitative study which involved thirty English teachers, teaching at high schools in Bireuen as the respondents. The data was collected using two sets of questionnaires and was analyzed using SPSS descriptive statistics. The results showed that the teachers mostly agreed with overall job-related beliefs; they were satisfied with their jobs; they had high self-efficacy and they received satisfying appraisals and feedbacks. Concerning impacts of beliefs, three namely: overal job-related beliefs, job satisfaction, and self-efficacy -—gave big impacts while the last principle, appraisals and feedbacks, only had a small impact. In conclusion, teahers in Bireun have positive beliefs and this gives positive impacts as well. So, the suggestion that can be made is that because of this positivity, the teachers are suggested to focus on self-improvement as educators such as participating in more teacher  development programs